Machining and meshing analysis of face gears by power skiving - Zhengyang HAN; Chuang JIANG; Xiaozhong DENG (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2022)
To improve the machining efficiency of face gears, a novel efficient machining method referred to as power skiving is applied to the machining of face gears and is presented in this paper. The processing principle of machining face gears by power skiving and the relative motion between the cutting tool and the face gears is discussed. Then, the mathematical models of the power skiving cutter with a fillet angle and the machining process by power skiving are established. The tooth flank equation of the face gears using the new processing method is derived. To describe the tooth flank structure, the difference between the tooth flank of power skiving face gears and traditional face gears, in which the surface is obtained by involute cylindrical gears, is compared, and a tooth flank contact analysis is conducted. The feasibility of the new processing method and the correctness of the mathematical model are verified by a power skiving experiment conducted on the face gear drive of a six-axis machine tool. Finally, the influence rule of the skiving cutter parameters on the meshing performance is analyzed in the process of machining face gears, and guidance is provided for the parameter design of power skiving cutting tools for face gears.